SCIENTIFIC COMPREHENSION OF THE NECESSITY OF PHARMACEUTICAL TOURISM DEVELOPMENT IN UKRAINE AND THE RESEARCH OF ORGANIZATIONAL AND ECONOMIC APPROACHES AS TO ITS IMPLEMENTATION IN THE HEALTHCARE SYSTEM (World Science, 2020)
The article proved that pharmaceutical tourism has been developed during a long period of time as an essen-tial part of medical tourism. The defined forms of activity have an integral character and contribute to the in-crease of the level of accessibility and quality of medical and pharmaceutical aid to the population outside their regular place of residence. The preconditions for activation the development of medical tourism and the necessity of being regarded as an independent activity of pharmaceutical tourism have been determined. In-stitutional components of pharmaceutical tourism (a subject, objects, subjects, forms of organization) have been outlined and described as well as the functions, which can be used on two levels: on the level of the government and the society, and in the system of pharmaceutical provision of the population and healthcare in general. The integral and dualistic character of pharmaceutical tourism as a modern activity in the system of healthcare has been substantiated. Taking into account modern tendencies as to globalization of national economics, imperfection of mechanisms of government regulation of the level of accessibility of pharmaceu-tical aid, increase of gap between different countries, groups of population or patients in the resource provi-sion of national systems of healthcare, the need for the development of medical and pharmaceutical tourism will continue in the future. It promotes the development of a complex program of their implementation in Ukraine.